DETERMINATION OF THE PRESSING FORCE OF THE HAULM TO THE BARS OF THE HAULM-REMOVING CONVEYOR WITH BEATER BLADES - Payziev Gaibulla Kadirovich; Salokhiddinov Nurmuhammad Satimbaevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In the article, on the basis of the theoretical studies carried out, the interaction of the blades of the bladed beater with the bars of the haulm-removing conveyor is given, and analytical dependencies are derived to determine the length of the beater blade, the force of pressing the tops to the bars of the haulm-removing conveyor.